Assessing the epithelial-to-mesenchymal plasticity in a small cell lung carcinoma (SCLC) and lung fibroblasts co-culture model - Dhungel, Nilu; Youngblood, Reneau; Chu, Min; Carroll, Jennifer; Dragoi, Ana-Maria (Frontiers in Molecular Biosciences, 2023)
The tumor microenvironment (TME) is the source of important cues that govern epithelial-to-mesenchymal (EMT) transition and facilitate the acquisition of aggressive traits by cancer cells. It is now recognized that EMT is not a binary program, and cancer cells rarely switch to a fully mesenchymal phenotype. Rather, cancer cells exist in multiple hybrid epithelial/mesenchymal (E/M) states responsible for cell population heterogeneity, which is advantageous for the ever-changing environment during tumor development and metastasis. How are these hybrid states generated and maintained is not fully understood. Here, we show that direct interaction between small cell lung carcinoma cells and lung fibroblasts induces a hybrid EMT phenotype in cancer cells in which several mesenchymal genes involved in receptor interaction with the extracellular matrix (ECM) and ECM remodeling are upregulated while epithelial genes such as E-cadherin remain unchanged. We also demonstrate that several core EMT-regulating transcription factors (EMT-TFs) are upregulated in cancer cells during direct contact with fibroblasts, as is Yes-associated protein (YAP1), a major regulator of the Hippo pathway. Further, we show that these changes are transient and reverse to the initial state once the interaction is disrupted. Altogether, our results provide evidence that tumor cells’ direct contact with the fibroblasts in the TME initiates a signaling cascade responsible for hybrid E/M states of cancer cells. These hybrid states are maintained during the interaction and possibly contribute to therapy resistance and immune evasion, while interference with direct contact will result in slow recovery and a switch to the initial states.